Long-term fatigue and quality of life among epithelial ovarian cancer survivors: a GINECO case/control VIVROVAIRE I study. (9th March 2019) - Joly, F; Ahmed-Lecheheb, D; Kalbacher, E; Heutte, N; Clarisse, B; Grellard, J M; Gernier, F; Berton-Rigaud, D; Tredan, O; Fabbro, M; Savoye, A M; Kurtz, J E; et al.
Abstract: Background: Few data are available on long-term fatigue (LTF) and quality of life (QoL) among epithelial ovarian cancer survivors (EOCS). In this case–control study, we compared LTF, symptoms and several QoL domains in EOCS relapse-free ≥3 years after first-line treatment and age-matched healthy women. Patients and methods: EOCS were recruited from 25 cooperative GINECO centers in France. Controls were randomly selected from the electoral rolls. All participants completed validated self-reported questionnaires: fatigue (FACIT-F), QoL (FACT-G/O), neurotoxicity (FACT-Ntx), anxiety/depression (HADS), sleep disturbance (ISI), and physical activity (IPAQ). Severe LTF (SLTF) was defined as a FACIT-F score <37/52. Univariate and multivariate logistic regressions were conducted to analyze SLTF and its influencing factors in EOCS. Results: A total of 318 EOCS and 318 controls were included. EOCS were 63-year-old on average, with FIGO stage I/II (50%), III/IV (48%); 99% had received platinum and taxane chemotherapy, with an average 6-year follow-up. There were no differences between the two groups in socio-demographic characteristics and global QoL. EOCS had poorer FACIT-F scores (40 versus 45, P < 0.0001), lower functional well-being scores (18 versus 20, P = 0.0002), poorer FACT-O scores (31 versus 34 P < 0.0001), and poorer FACT-Ntx scores (35 versus 39, P < 0.0001). They also reported more SLTF (26% versus 13%, P = 0.0004), poorer sleep quality (63% versus 47%, P = 0.0003), and more depression (22% versus 13%, P = 0.01). Fewer than 20% of EOCS and controls exercised regularly. In multivariate analyses, EOCS with high levels of depression, neurotoxicity, and sleep disturbance had an increased risk of developing SLTF ( P < 0.01). Conclusion: Compared with controls, EOCS presented similar QoL but persistent LTF, EOC-related symptoms, neurotoxicity, depression, and sleep disturbance. Depression, neuropathy, and sleep disturbance are the main conditions associated with severe LTF.